Investasi di Sektor Pertambangan dan Tingkat Partisipasi Angkatan Kerja Sebagai Determinan Pertumbuhan Ekonomi di Kalimantan Selatan - Ratnaningsih Hidayati (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2021)
Investment and labor are factors that affect the economic growth of a region. Economic growth is measured by Gross Regional Domestic Product (GRDP). The purpose of this study is to explain the effect of investment in the mining sector and the labor force participation rate on the GRDP of South Kalimantan. This study employs a quantitative approach with secondary data on macroeconomic indicators obtained from the Central Statistics Agency of South Kalimantan. The data used is panel data which is a combination of time series data with cross-section data. The estimation results of the Fixed Effect Model show that foreign investment, domestic investment, and the level of labor force participation simultaneously have a significant effect on economic growth in South Kalimantan. Partially, foreign investment on mining sector has a negative and insignificant effect; domestic investment on mining sector has a positive and significant effect, and Labor Force Participation Rate has a negative and significant effect on economic growth in South Kalimantan